High Estradiol Levels are Associated with Increased Mortality in Older Men Referred to Coronary Angiography - Lerchbaum, E.; Pilz, S.; Grammer, T. B.; Boehm, B. O.; März, W.; Obermayer-Pietsch, B. (Experimental and Clinical Endocrinology & Diabetes, 2011)
There is evidence showing an important role of estrogens in men’s health. We aimed to evaluate whether estradiol levels are associated with overall mortality and specific fatal events.We measured estradiol levels in 2 078 men who were routinely referred for coronary angiography (1997–2000).The main outcome measures were Cox proportional hazard ratios (HRs) for mortality from all causes, from cardiovascular and non-cardiovascular causes including cancer according to estradiol levels.Multivariable HRs (with 95% confidence intervals) for all-cause, non-cardiovascular, and cancer mortality were 1.43 (1.08–1.91), 2.11 (1.34–3.34), and 2.27 (1.00–5.19), respectively, in the fourth estradiol quartile as compared to the first. There was no significant association of estradiol levels with cardiovascular mortality. In multivariate adjusted analyses, higher estradiol levels in men were significantly associated with prevalent strokes, peripheral vascular disease, and carotid artery stenosis compared to lower estradiol levels.High levels of estradiol are associated with all-cause and non-cardiovascular mortality in a large cohort of older men referred to coronary angiography. Further studies are warranted to confirm our results and to elucidate the underlying mechanisms.
Keywords: estradiol; mortality